Climate anxiety: What predicts it and how is it related to climate action?. (October 2022) - Whitmarsh, Lorraine; Player, Lois; Jiongco, Angelica; James, Melissa; Williams, Marc; Marks, Elizabeth; Kennedy-Williams, Patrick
Abstract: As scientific evidence of the severity of climate change increases, there are indications that this represents a significant psychological burden in the form of climate anxiety on the public. So far very little research has explored the prevalence, predictors, or effects of climate anxiety amongst the public. This study aims to address this gap by exploring climate anxiety in the UK. It addresses the following questions: (a) How prevalent is climate anxiety amongst adults in the UK? (b) What are the predictors of climate anxiety? and (c) Does climate anxiety predict climate action? We report on findings from an online survey of the UK public ( N = 1338) undertaken in late 2020 (partially replicated in May 2022 with a sub-sample of 891 respondents) which found that while there are high levels of concern about climate change, there are low levels of climate anxiety (measured using the Climate Change Anxiety Scale). Climate anxiety was higher amongst younger age groups, those with higher climate concern, higher generalised anxiety, lower mindfulness, higher nature relatedness, and more climate change information seeking behaviour. In addition, climate anxiety predicted some (but not all) types of pro-environmental action. Consistent with other recent research, these findings indicate that climate anxiety may not necessarily be a negative impact of, or maladaptive response to, climate change; but rather, at least to some degree, be a motivating force for effective action. Highlights: First detailed study of climate anxiety amongst UK adult population. Climate change worry is widespread, but climate anxiety levels far lower. Climate anxiety correlates with higher generalised anxiety and lower mindfulness. Strongest predictor of climate anxiety is climate information seeking behaviour. Climate anxiety positively predicts some but not all pro-environmental actions.